Natural convection heat transfer in a circle-square annulus using lattice Boltzmann method- Treatment of curved boundary conditions. (October 2019) - Hooshmand, Payam; Khakrah, Hamidreza; Jamalabadi, Mohammad Yaghoub Abdollahzadeh; Ross, David
Highlights: The free convection flow and heat transfer are analyzed. The lattice Boltzmann method is employed. The local and total entropy generation is utilized. The Koo-Kleinstreuer-Li model is used for thermal conductivity. Abstract: The lattice Boltzmann simulation of natural convection fluid flow and heat transfer in a square-circle annulus is carried out. A comprehensive discussion regarding the treatment of curved boundary condition for temperature and velocity is presented. The annulus is filled with CuO-water nanofluid. The dynamic viscosity of nanofluid is estimated using KKL (Koo-Kleinstreuer-Li) model. The second law analysis is added to the investigation order to show the effect of different parameters on the irreversibility. The Rayleigh number (10 3 ≤Ra≤10 6 ), nanoparticle concentration (0 ≤ ϕ ≤ 0.04) and the aspect ratio of inner square cylinder are the governing parameters. The influence of the mentioned parameters on the nanofluid flow, temperature field, local and total entropy generation, Bejan number and average Nusselt number are presented, comprehensively. Graphical abstract: Image, graphical abstract